Imagery and meaning creation of Azerbaijani school poets with stringed instruments - Mohammad Parsanasab; Masoud Moazami Goodarzi (مجله مطالعات ایرانی, 2023)
Introduction The poets of Azerbaijan school are famous for using meta-poetic information and common knowledge of their time. One of the arts that appears in the court of these poets is music. Falaki Sharvani, Mojiruddin Beilaqani, Nizami Ganjavi and Khaqani Sharvani are four poets of almost the same period, each of them created imagery and meaning with musical instruments, using their interest, knowledge and ability to compose poems. The purpose of this research is to find out the level of knowledge and understanding of each poet about musical instruments and to compare the aesthetics and meaning of the poems that each of them wrote by using this type of musical instruments. The musical knowledge of each poet, the extent of their knowledge of the musical instruments of their time, the ability and level of creativity of each poet in depicting the way of playing and different components of an instrument, knowing the time and place situations where the people of that time used all kinds of instruments; It is one of the findings of this research. The comparison of sample verses written by the four mentioned poets with various stringed-wound instruments leads to the results, the most important of which are: The instrumental art of every poet, understanding the variety and quality of images made with instruments, identifying narrow-minded, creative and innovative poets in creating fresh and pristine images and meanings with instruments. Of course, in the end, according to the attitude of each poet towards musical instruments, the hypothesis of being a musician or at least a musicologist can be put forward. Methodology Examining the aesthetics and meaning creation with stringed musical instruments in some verses extracted from Divan of the poets in question, as well as comparing the art of each of them in creating pure and beautiful images and fresh and pristine concepts is the most important issue that we face in this research.Using library resources and two methods of structural studies and content analysis, this research deals with the description and analysis of subject images in the Divan of poets of Azerbaijan school and gives significant quantitative and qualitative results. Discussion By carefully examining the divan of the poets of the Azerbaijan School, twelve types of stringed instruments have been used as a tool for illustration and theme development. In order to better organize and order the contents, the poetic evidences of the poets in question are given under the headings of instruments. Harp is one of the oldest stringed instruments that has been commonly played in Iran since before Islam. Among the four poets examined in this research, the "harp" instrument is the most used in Nizami’s poems, but the images presented by Khaqani are more novel and debatable. In the term of music, "Rood" is one of the ancient stringed instruments with strings, which are not commonly played today. Poets have considered various meanings and concepts by using this word. Among the examined poets, Nizami can be considered the only poet who knows and is familiar with this instrument, so that in Nizami's poems, this word has the highest frequency among all the instruments used in the divan of all four poets. In terms of music, “Rabab” is a family of stringed and plectrum instruments, or in other words, a field whose various types can be found in every corner of Iran from the past to the present day. None of the examined poets were strangers to the “Rabab” instrument, but in the meantime, Khaqani has created more and more beautiful images. Of course, Mojir's contribution is also after Khaqani and more than Nizami, and the imagery along with the themes of Mojir's advice with this instrument cannot be ignored. The variety of imagery and imagination of Khaqani with the “Barbat” is more than his other contemporaries. Setar is one of the stringed instruments that today has four strings. This instrument is mostly mentioned as "Seta" in literary texts, especially in the 6th century. Khaqani illustrated four verses of his divan with “Setar” and “Seta”, three verses of which are among the poems and one verse of which is included in his compositions. In terms of comparison, Mojir Beilaqani's poem is somewhat close to Khaqani's from an aesthetic point of view, but the verses of Nizami have more of a narrative aspect and are devoid of significant rhetorical beauty. Among all the poems of the researched poets, only one verse of Mojir Beilaqani can be used to imagine a type of musical instrument from the word "Zir". Kamancheh is one of the stringed instruments that is played with fiddlestick. Today, this instrument is one of the common instruments that many people use both as a soloist and as a band playing. Khaqani used this word twice in his poems and both times with the additional combination of "rebab's fiddle", which undoubtedly meant the same arshe or rebab's fiddle. “Mezhar” is an Arabic name and in most dictionaries and music dictionaries, as well as the opinions and thoughts of music researchers, it is considered to be a family of stringed instruments from the category of Harp or Barbat. Falaki and Nizami have not used this word. Mojiruddin Beilaqani and Khaqani have illustrated with this instrument twice in their poems. "Qanun" is the name of an absolute stringed instrument that is still played today, and in appearance, it is in the shape of a right-angled trapezoid, almost similar to the “Santoor”, but it is most likely older than that. Some have attributed its construction to Farabi. Among the four considered poets, Nizami is the only poet who, among the various meanings of "qanun", considered its musical aspect and illustrated with it. Other poets of the Azerbaijani school have not explicitly addressed the musical meaning of this word. "Tanbur" is one of the instruments that is widely used even today, especially in the western regions of the country and Kurdistan. The only poetic evidence of this instrument in the poetry of the Azerbaijani school is a verse written by Nizami in the poem "Khosro and Shirin" and in one of Khosrow's debates with Shirin:I have not been canny in love with youTo come to your neighborhood with a "Tanbur”(Nizami, 1388, Volume 1: 290) Conclusion By examining and analyzing the sample poems of Azerbaijani school poets, we find out that Harp, Rabab, Rood, and Barbat instruments are among the stringed instruments that have the most frequency in the divan of the discussed poets.The repetition rate of each of these four instruments alone is even higher than the total frequency of the other eight stringed instruments, and this shows their use and importance in Azerbaijani style poetry. From this statistical comparison, we can find out some important points:1- The low frequency of stringed instruments in the divan of Falaki and Mojiruddin Beilaqani's poems shows that these two poets were not very interested in writing poetry in the field of music, in other words, they are one of those poets who are not concerned with music. Of course, Mojir Beilaqani's musical knowledge is far more than that of Falaki.2- On the other hand, if we cannot or do not want to call Mojir and Falaki, Nizami and Khaqani musicians, then we are forced to call them musicologist poets. They have a high level of musical understanding, both statistically and literary, as discussed in the text of the research.3- The high frequency of sample verses in the poetry of the poets in question with the instrument "Harp" shows that this instrument was very popular in that historical period and in the geographical region of Sharvan and Arran at that time. This point can be a reason for the spread and prevalence of playing the “Harp” in that erea.Khaqani Sharvani is the most image-creating poet of this group, whose range of literary arrays and frequency and type of use are more abundant and distinct than other poets. From the point of view of meaning creation, it can be said that in the few verses that he wrote with stringed instruments, Falaki sharvani has mostly praised his praise. He has used less knowledge and other sciences in composing his poems. Mojiruddin Beilaqani is also a praiseworthy poet, but unlike Falaki, he uses musical instruments. Variety in Concept processing makes his speech more pleasant. In this way, in addition to his astronomical knowledge, he has also entered into religious, philosophical and wisdom issues. The content of most of the verses he wrote with stringed instruments is advice and admonition. Perhaps it can be said that in terms of moral and philosophical conclusions, none of his contemporary poets have done as well as him.But about Nizami Ganjavi, it can be said that according to the Masnavi poetic form that he used, his poetry is different from the other three poets in terms of form and meaning. The audience, faced with the narrative and story of Nizami style, should prepare themselves to enter a long and continuous story, so reading a verse from him without considering the vertical connection of the verses is not a favor. Khaqani's poetry is more prominent in its comprehensiveness and breadth of meanings and themes than the other three poets. Deep thinking and subtlety is a characteristic of Khaqani's poetry, which sometimes leads to the creation of novel and new meanings and concepts. simulating musical instruments to living things is a feature that is rarely seen in the poetry of other poets of his time.